Assessment of city territory providing with objects of social, anthropogenous and tourist infrastructure by GIS (on the example of the city of Kharkiv) - Klychko, L.; Chuev, O.; Mazurova, A.; Telebeneva, E. (Cambridge: “Cambridge University Press”, 2016)
This paper evaluated the city of Kharkiv ensure real social, human and tourism infrastructure in 27 categories. Using geoinformation approach that involves the use of leading GIS tools identified such laws and phenomena, the study of which is impossible using only general scientific methods
Keywords: objects; objects of anthropogenous; infrastructure; geoinformation approach of GIS tools